Software educacional: simulador de ventilação mecânica e seus efeitos hemodinâmicos - Campos Junior, Moyses de (2022)
Introduction: Mechanical ventilation has its management considered highly complex, its virtual simulation provides a safe environment for the teaching of clinical situations and its cardiopulmonary interaction. Objective: Develop an educational software mechanical ventilation simulator with hemodynamic interaction. Material and Methods: The software was developed in the Web Technology Hypertext Markup Language version 5 and its evaluation (of content and format) was carried out after signing the Free and Informed Consent Form by the volunteers. The evaluation of cognitive gain and perception was made in fifth-year medical students 10 questions for the pre and posttest, 17 assertive for the instrument of perception on a Likert scale of agreement of five points and fields for comments. Its technical quality has been evaluated by an engineer and its content by experts. Results: The simulator developed provided references, choice of clinical situations and ventilation parameters, ventilatory and hemodynamics monitoring, arterial blood gas and animations. The technical quality of the software was approved by the engineer. The evaluation of the content of the simulator by seven experts obtained in the assertions the general average of the Likert (L) and concordance (Co) points: "excess content" (L = 3.14 and Co = 28.6%), "easy to use" (L = 3.43 and Co = 71.4%), and for the others (L >= 4.00 and Co >= 71.4%). The average content validation index was 0.86. In online activity, 26 students agreed to participate in the survey. The mean and standard deviation of correct answers in the questions by the students was in the pre-test of 12.4±4.74 and 20.2±3.97 in the post-test, t-test with a value of p <0.001. The linear correlation between the perception of the experts and the students was strong and positive about the use of the software. Experts suggested changes in software and students in didactics. Discussion: The viable changes in the simulator suggested by the experts were made. The students' comments contributed to adapt the didactics of the activity. The evaluation of the experts and the cognitive gain obtained in students suggests that the software has potential as a didactic resource in the teaching process of learning mechanical ventilation and its cardiopulmonary interaction